Perception Of Factors Promoting Cybercrimes Among Undergraduates In Delta State - Ikechukwu.E. ANUKWU; Ajibade. E. JEGEDE; Emmanuel. O. AMOO; David. O. IMHONOPI; GEORGE Tayo Ola; EGHAREVBA Matthew E; Godwin. E. EGBE; Elizabeth AROGBONLO (Communications of International Proceedings, 2021)
The trend in crime participation in recent times revolves around the use of information communication technology (ICT) for its perpetuation; this development has also accommodated different types of vices, such as crime, and the major one trending today, especially in Nigeria, is cyber-crime. The problem of cyber-crime today in Nigeria has been the increase in financial losses yearly. This study adopted a survey design; simple random sampling technique was used to select 391 respondents from Three Higher institutions in Delta State: Descriptive statistics was employed, to analyze data. The findings of this study identified weak societal values, Laziness, and societal pressure as the major factors that propel undergraduate student's involvement in cyber-crime. However, the following recommendations based on the findings were given in this study: There is a need for a value Re-orientation through the diverse social institutions the family, which is the first point of a child's orientation, should ensure that good morals and values are inculcated to their young ones growing and going into the higher institutions. There should be increased internet security to help protect data; this would help curb youth interest in cyber-crime.
Keywords: Cybercrime; Youths; Involvement; Undergraduates; Higher Institutions